The Analysis of Students’ Ability of Decimal Numeral Multiplication of the Fifth Grade Students - Made Suwariyasa (Journal of Psychology and Instruction, 2017)
This study aimed to (1) describing Learning multiplication of decimal fractions in V grade,(2) The students' ability in completing the multiplication of decimal fractions, (3) The constraints which were faced by students in completing the multiplication of decimal fractions and the solutions to overcome those obstacles. The type of this study was descriptive quantitative and qualitative research. The subjects of this study were the fifth grade students of SD Negeri 2 Penarukan, consisted of 20 students and teachers in V class. The object of this study were (1) Learning multiplication decimal fraction in V grade, (2) The students' ability in completing the multiplication of decimal fractions, (3) The constraints which were faced by students in completing the multiplication of decimal fractions and the solutions to overcome those obstacles. The observation, test, interview, and documentation were used to collect the data. The data were analyzed using descriptive quantitative and qualitative approach. The results showed (1) Learning multiplication decimal fractions was categorized good with a value of 84 , (2) the average test results in classical 59.9 with low category with the highest indicators is to solve everyday problems which involves multiplication of various fractions 55.25% and the lowest indicator is determining the results of multiplication operations of various fractional 88.5 %, (3) The constraints faced by students are: forget the concept of decimal fractions multiplication operations, forget to put coma at the end of the answer and students are still confusein completing the essay task. The solution to overcome those constraints aregiving students a lot of exercises regarding the multiplication of decimal fractions. So that students are better trained and familiar with the particular multiplication exercises.